The effect of tick salivary proteins on innate immunity cells - Páleníková, Jana (Jihočeská univerzita, 2016)
Saliva of Ixodid ticks contains a whole array of pharmacologically active molecules with vasodilatory, antihemostatic, and immunomodulatory activities. This thesis focuses on two types of salivary proteins, serpins and cystatins, and their role in immunomodulation. These protease inhibitors are known to affect many biological functions. To better understand their role in tick saliva we examined their effect on dendritic cells and their ability to modulate the immune response after pathogen infection. As model pathogens, Borrelia spirochetes and tick-borne encephalitis virus were used.
The effect of tick salivary proteins on innate immunity cells
Keywords: klíštěcí sliny přirozená imunita dendritické buňky buněčná signalizace; tick saliva innate immunity dendritic cells cell signaling